Winter matters: Sensitivity to winter climate and cold events increases towards the cold distribution margin of European beech (Fagus sylvatica L.). (10th October 2018) - Weigel, Robert; Muffler, Lena; Klisz, Marcin; Kreyling, Juergen; van der Maaten‐Theunissen, Marieke; Wilmking, Martin; van der Maaten, Ernst
Abstract: Aim: The dominant forest tree in Europe, European beech ( Fagus sylvatica L.), covers large areas of continental Europe and thus experiences diverse climatic conditions. In the face of predicted climate change and shifts of distribution ranges, it is important to understand the diverse climate–growth relationships towards distribution margins. Beech is generally reported to be sensitive to summer drought towards dry and continental regions; yet, few studies have investigated climate sensitivity towards the cold distribution margin of beech. We hypothesized that at colder sites (a) growth of beech is more sensitive to winter cold, (b) growth is less influenced by summer drought, and (c) stand‐wide growth reductions (negative pointer years) are related to extreme winter cold events. Taxon: European beech ( Fagus sylvatica L.). Location: A large gradient of decreasing winter temperature (ΔT >4 K along 500 km) from Rostock (Germany) to Gdańsk (Poland). Methods: We analysed climate–growth relationships and the nature of growth reductions of 11 beech stands from more central to cold marginal beech populations. Results: Towards the cold marginal populations, growth became increasingly sensitive to winter cold (February temperature) and less sensitive to summer water availability (June precipitation). Likewise, negative pointer years coincided with winter cold anomalies at the colder sites and with summer drought anomalies at the warmer sites. Thus, over the studied gradient, the general sensitivity of beech to summer drought transitions into sensitivity to winter cold. Main conclusions: A range shift of beech across the current cold distribution margin is often assumed to compensate for habitat and productivity losses of drought‐prone southern and central populations. With respect to the winter cold sensitivity found in our study, such assumptions should be taken with caution. Since winter cold events are predicted to persist with similar frequency and magnitude even during predicted climate warming, beech populations in the newly colonized habitat might be significantly sensitive to winter cold.